PENERAPAN SISTEM MANAJEMEN MUTU PADA LABORATORIUM PREPARASI PLTR-BATAN - Ruthman Sipahutar; Daniel Sembiring; Abdul Haris Lahuddin (LPPM, 2011)
Laboratory Preparation and Analysis PLTR-BATAN to increase competitiveness to competitor hence have to upgrade service and made a pitch for sertifikasi from KAN party/ side ( Committee Accredit National) so that by pocketing certificate from given by school institute is the easiness, hence more interesting to cutomer/ client party/ side to use service from the laboratory. Problems faced by PLTR-BATAN party/ side ( Technological Center of Waste Radioactive - Body Nuclear Energy National) is in order goals laboratory service product marketing for the analysis of examination less / do not reach . Goals research into which is done/conducted by at PLTR-BATAN. laboratory is : to reach order goals by way of existence of laboratory accreditation from KAN party/ side ( Committee Accredit National) as according to ISO document / iec 17025:2005, giving proposal in management system quality. Keywords : Management system quality of control, management standard quality of ISO 9000, IEC 17025 : 2005